Acute and Chronic Wound Fluid Inversely Influence Wound Healing in an in-Vitro 3D Wound Model - Besser, Manuela; Khosravani, Milad; Severing, Anna-Lena; Rembe, Julian-Dario; Stuermer, Ewa Klara (Journal of Tissue Repair and Regeneration, 2017)
If a wound progressively heals or the healing process is impaired is basically influenced by the surrounding milieu. This is reflected by the wound fluid. Its specific composition triggers the migration, proliferation and differentiation of dermal and epidermal cells which so far was not sufficiently examined in 2D cell culture models. The influence of the different wound entities was analyzed on a newly implemented three dimensional in-vitro model, which improved the transferability to the in-vivo situation. The influence of pooled wound fluids from patients suffering from acute or chronic wounds were investigated within a time period of 10 days after wound application. Histological and immunohistochemical analyses were performed addressing the impact of AWF and CWF on regeneration, such as cell proliferation, fibroblast activity and cell migration. AWF slightly stimulated fibroblast migration while CWF inhibited their activation and migration. The CXCR4- immunopositive population was continuously decreased compared to the control and AWF treatment. The expression of FAP was enhanced under AWF and medium. In keratinocytes CWF massively stimulated cell proliferation initiating on day six after injury. The presence of 10% CWF inhibited fibroblast activation and migration and induced the degradation of the collagen matrix. Keratinocytes were stimulated to proliferate, resulting in healing inhibiting hyperplasia. Transferred to human wounds, no effective wound closure would be achieved because of the de-regulation of pro-proliferative and migration-stimulating factors and a degraded extracellular matrix. This newly implemented 3D study model represents a novel appropriate in-vitro system for studying healing mechanisms and potential therapeutic applications.
Keywords: 3D wound model; keratinocyte; fibroblast; CXCR4; FAP; acute and chronic wound fluid; wound healing